Pembuatan Direktori Alat Musik Tradisional Minangkabau - Putri, Ezy Nilda; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract This article is about making directory of the musical instrument traditional Minangkabau. The purpose of this article are: (1) to describe making directory of the musical instrument traditional Minangkabau, and (2) to describe obstacle and solution of making directory of the musical instrument traditional Minangkabau. This article use descriptive method with observation, interview, and read the literature. Base on result of making directory of the musical instrument traditional Minangkabau, the conclution is. First, making the directory of the musical instrument traditional Minangkabau the steps are: (a) collecting the data about the musical instrument traditional Minangkabau; (b) arrange the data base on alphabet; (c) typing the data with Microsoft Publisher; and (d) designing the cover of directory of the musical instrument traditional Minangkabau. Second, the obstacle in making directory of the musical instrument traditional Minangkabau are: (a) the lack of knowledge about the musical instrument traditional Minangkabau; (b) the difficult thing when collected the data about the musical instrument traditional Minangkabau; (c) the difficult thing when designed layout of directory the musical instrument traditional Minangkabau. Solution of this problem are: (a) collected the data from some literature andÂ  to the institute that has data about the musical instrument traditional Minangkabau; (b) direct observation about data to get information about the musical instrument traditional Minangkabau; and (c) designed the layout with simple and not use more colour.Keywords: directory, instrument traditional, Minangkabau